The vocabulary quilt as a cooperative learning strategy to develop writing skills amongst ninth year of basic education studentsat Pio Jaramillo high school. 2014-2015 academic period - Malacatus Calva, Rosa Jaqueli (2016)
The current research work was designed to determine the effect of cooperative learning strategy called Vocabulary Quilt to improve writing skills amongst ninth year students at Pio Jaramillo Alvarado high school. In the development of the same were used the following methods, scientific, descriptive, analytic-synthetic and statistic. Furthermore, the results of posttest revealed a significant progress in the students’ performa nce in writing skills through implementation of Vocabulary Quilt and the answers received of the questionnaires showed that the students work in a cooperative way. During eight weeks were into account to improve writing skills through implementations of intervention plans. Finally, the researcher concluded that the application of Vocabulary Quilt as a strategy of cooperative learning was relevant to improve writing skills in the ninth year, for this reason is important that the teachers work in a cooperative way, through of this, students writing skills will improve